HBV DNA Integration and Clonal Hepatocyte Expansion in Chronic Hepatitis B Patients Considered Immune Tolerant - Mason, William S; Gill, Upkar S; Litwin, Samuel; Zhou, Yan; Peri, Suraj; Pop, Oltin; Hong, Michelle L W; Naik, Sandhia; Quaglia, Alberto; Bertoletti, Antonio; Kennedy, Patrick T F (Gastroenterology (New York, N.Y. 1943), 2016)
Chronic infection with hepatitis B virus (HBV) progresses through different phases. The first, called the immune-tolerant phase, has been associated with a lack of disease activity. We examined HBV-DNA integration, clonal hepatocyte expansion, HBV antigen expression, and HBV-specific immune responses in patients in the immune-tolerant phase to assess whether this designation is appropriate or if there is evidence of disease activity. We studied HBV-DNA integration, clonal hepatocyte expansion, and expression of hepatitis B surface antigen and core antigen in liver tissues from 26 patients with chronic HBV infection (ages, 14-39 y); 9 patients were positive for hepatitis B e antigen (HBeAg) in the immune-tolerant phase and were matched for age with 10 HBeAg-positive patients with active disease and 7 HBeAg-negative patients with active disease. Peripheral blood samples were collected and HBV-specific T cells were quantified for each group. Detection of HBV antigens differed among groups. However, unexpectedly high numbers of HBV-DNA integrations, randomly distributed among chromosomes, were detected in all groups. Clonal hepatocyte expansion in patients considered immune tolerant also was greater than expected, potentially in response to hepatocyte turnover mediated by HBV-specific T cells, which were detected in peripheral blood cells from patients in all phases of infection. We measured HBV-specific T cells, HBV-DNA integration, and clonal hepatocyte expansion in different disease phases of young patients with chronic hepatitis B, with emphasis on the so-called immune-tolerant phase. A high level of HBV-DNA integration and clonal hepatocyte expansion in patients considered immune tolerant indicated that hepatocarcinogenesis could be underway-even in patients with early stage chronic HBV infection. Our findings do not support the concepts that this phase is devoid of markers of disease progression or that an immune response has not been initiated. We propose that this early phase be called a high-replication, low-inflammation stage. The timing of therapeutic interventions to minimize further genetic damage to the hepatocyte population should be reconsidered.